Effects of dietary sulfated polysaccharides extracted from brown macroalgae Sargassum ilicifolium on growth indices, antioxidant status, and immune genes expression in white shrimp (Litopenaeus vannamei) - Maryam Pourazad; Dara Bagheri; Ebrahim Sotoudeh; Ahmad Ghasemi (Aquaculture Reports)
This feeding trial aimed to evaluate the impacts of dietary sulfated polysaccharides extracted from brown macroalgae Sargassum ilicifolium on growth, antioxidant status, and immune genes expression in white shrimp, Litopenaeus vannamei. A total of 225 shrimp (3.91 ± 0.02 g) were stocked into fifteen 300-L fiberglass tanks (15 shrimp/tank) and divided into five groups fed diets supplemented with 0 (control), 0.5 (SIP0.5), 1 (SIP1), 2 (SIP2), and 4 (SIP4) g/kg diet of S. ilicifolium-extracted sulfated polysaccharides (SIP). After 8 weeks, growth and feed utilization indices and muscle composition in white shrimp were not significantly different (P > 0.05). All shrimps exhibited a high survival (above 80 %). While catalase and glutathione S-transferase (GST) activities in the hepatopancreas of shrimp were not significantly different among treatments, hepatopancreas glutathione (GSH) content of shrimp fed diet supplemented with 4 g SIP/kg diet (SIP4) was significantly higher, then SIP2 treatment, and lower in other shrimps (P < 0.05). Also, incorporating 4 g SIP/kg diet resulted in a significant lower malondialdehyde (MDA) content in the hepatopancreas of shrimp than the control (P < 0.05). Prophenoloxidase relative expression was highest in the hepatopancreas of shrimp fed diet supplemented with 2 g/kg of S. ilicifolium-extracted sulfated polysaccharides (SIP2), followed by 0.5 and 1 g/kg SIP fed treatments, then 4 g/kg SIP fed group and lowest in the control (P < 0.05). The higher relative expressions of SOD and penaeidin-3a genes in the hepatopancreas were also seen in the SIP fed shrimps. Moreover, a significant increase in hepatopancreas lysozyme expression was recorded with increasing SIP administration levels. Thus, sulfated polysaccharides extracted from S. ilicifolium at levels of 2–4 g/kg diet have antioxidant and immunostimulatory effects in white shrimp and can be safely used as an immunostimulant for juvenile L. vannamei without impairing growth performance and biochemical muscle composition.